2021
DOI: 10.3390/cancers13174444
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Tumor Vasculature to Reduce Hypoxia, Enhance Perfusion, and Optimize Therapy Uptake

Abstract: A basic requirement of tumorigenesis is the development of a vascular network to support the metabolic requirements of tumor growth and metastasis. Tumor vascular formation is regulated by a balance between promoters and inhibitors of angiogenesis. Typically, the pro-angiogenic environment created by the tumor is extremely aggressive, resulting in the rapid vessel formation with abnormal, dysfunctional morphology. The altered morphology and function of tumor blood and lymphatic vessels has numerous implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 153 publications
(161 reference statements)
1
36
1
Order By: Relevance
“…Agents targeting the angiopoietin pathway, such as trebananib, and the TGF-ß pathway, such as tasisulam, have been met with limited clinical success [ 85 , 86 , 87 , 120 ]. The normalization of tumor vascularization through the upregulating of thrombospondin-1and the promotion of smooth muscle cell proliferation and migration in conjunction with EC apoptosis could potentially regulate therapeutic intratumoral drug delivery, enhancing efficacy [ 121 , 122 ]. Drug development in this area appears promising, but remains in pre-clinical stages at present [ 123 ].…”
Section: Angiogenesis Inhibitors In Gynecologic Cancers: Carving a Ne...mentioning
confidence: 99%
“…Agents targeting the angiopoietin pathway, such as trebananib, and the TGF-ß pathway, such as tasisulam, have been met with limited clinical success [ 85 , 86 , 87 , 120 ]. The normalization of tumor vascularization through the upregulating of thrombospondin-1and the promotion of smooth muscle cell proliferation and migration in conjunction with EC apoptosis could potentially regulate therapeutic intratumoral drug delivery, enhancing efficacy [ 121 , 122 ]. Drug development in this area appears promising, but remains in pre-clinical stages at present [ 123 ].…”
Section: Angiogenesis Inhibitors In Gynecologic Cancers: Carving a Ne...mentioning
confidence: 99%
“…In peritumoral stroma, lymphatic vessels appear to be inflamed and dilated, which serve as the functional route for cancer-cell dissemination ( Figure 4 a,b). By contrast, the existence of lymphatic vessels in intratumoral areas is ambiguous, and the majority of the lymphatic vessels in intratumoral areas are sparse, dysfunctional, collapsed vessels with a long narrow or atretic shape ( Figure 4 c), which is unfavorable for lymph draining or cell migration [ 90 ]. These destructing lymphatics may contribute to increasing the compressive stress within tumor areas [ 91 , 92 ].…”
Section: Morphology Of Tumor-associated Lymphatic Vesselsmentioning
confidence: 99%
“…For example, Kruger et al [ 100 ] showed that a high baseline microvessel density was significantly associated with the response to bevacizumab. However, tumor vasculatures are dysfunctional, leading to immunosuppression and therapy resistance in the vast majority of cases, and normalizing the tumor vasculature can optimize drug uptake [ 90 ].…”
Section: Lymphatic Vessel Density (Lvd)mentioning
confidence: 99%
“…Anti-angiogenic therapies can normalize tumor vasculature, uniformly increase oxygen delivery and reverse the hypoxic areas of the tumor. This allows for better uptake and distribution of therapeutic drugs to the tumor ( 203 ). Many anti-angiogenic therapies work by inhibiting VEGF, either by directly binding to VEGF or inhibiting the VEGF receptor.…”
Section: Reversal Of Hypoxia As An Approach To Personalized Therapymentioning
confidence: 99%